PROXIMATE CHEMICAL COMPOSITION OF MUD CRAB (Scylla serrata) SHELL FLOUR - Ramadhani, Nuzul Ria; Karnila, Rahman; Edison, Edison (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT This research aims to determine the proximate chemical composition of the mud crab (Scylla serrata) shell flour. The parameter measured is proximate composition (moisture, ash, protein, fat, and carbohydrate content). The research method consists of two stages: 1) preparation of mud crab shell flour. 2) proximate analysis of mud crab shell flour. The result showed that the proximate chemical composition contained in the mud crab shell flour of moisture, ash, protein, fat, and carbohydrate content was 5,27% (WW), 63,09% (DW), 13,23% (DW), 0,77% (DW) and carbohydrate 22,91 % (by difference), respectively. Keywords: proximate analysis, mud crab shell, flour preparation